REFORMA AGRARIA ANTARA HARAPAN DAN REALITA - Zaidar (Faculty of Law, Universitas Brawijaya, 2021)
Indonesian Constitutional Law stated in Article 33 paragraph (3) concerning the use of Land, natural resources which controlling by the State in order to achieve the greatest prosperity for the whole citizens. These basic values require the fulfillment of people's rights to be able to access various agrarian resources. In reality, what was expected (das sein) has not been realized. Many problems iii land have not been resolved until now. Control and ownership of extensive land for some people (owner of capital)resulted in the marginalization of community rights, resulting in social conflicts, which in the end, in a matter of time, the impoverishment process occurred. This condition indicates that there is no justice and welfare for the people. The regulation of agrarian resources and ignores the Basic Agrarian Law (UUPA) tends to side with the owners of capital. Various irregularities with the UUPA, as well as the absence of the concept of the Right to Control the state asdesired by Article 33 Paragraph (3) of the 1945 Constitution, have prompted the birth of the People's Consultative Assembly Decree. No. IX of 2001 concerning Agrarian Reform and Natural Resource Management, it is unfortunate that Agrarian Reform which is expected to date has not been fullyrealized.